Focused methane migration formed pipe structures in permeable sandstones: Insights from uncrewed aerial vehicle‐based digital outcrop analysis in Varna, Bulgaria. Issue 6 (24th May 2021) - BÖttner, Christoph; Callow, Ben J.; Schramm, Bettina; Gross, Felix; Geersen, Jacob; Schmidt, Mark; Vasilev, Atanas; Petsinski, Petar; Berndt, Christian
Abstract: Focused fluid flow shapes the evolution of marine sedimentary basins by transferring fluids and pressure across geological formations. Vertical fluid conduits may form where localized overpressure breaches a cap rock (permeability barrier) and thereby transports overpressured fluids towards shallower reservoirs or the surface. Field outcrops of an Eocene fluid flow system at Pobiti Kamani and Beloslav Quarry ( ca 15 km west of Varna, Bulgaria) reveal large carbonate‐cemented conduits, which formed in highly permeable, unconsolidated, marine sands of the northern Tethys Margin. An uncrewed aerial vehicle with an RGB sensor camera produces ortho‐rectified image mosaics, digital elevation models and point clouds of the two kilometre‐scale outcrop areas. Based on these data, geological field observations and petrological analysis of rock/core samples, fractures and vertical fluid conduits were mapped and analyzed with centimetre accuracy. The results show that both outcrops comprise several hundred carbonate‐cemented fluid conduits (pipes), oriented perpendicular to bedding, and at least seven bedding‐parallel calcite cemented interbeds which differ from the hosting sand formation only by their increased amount of cementation. The observations show that carbonate precipitation likely initiated around areas of focused fluid flow, where methane entered the formation from the underlying fractured subsurface. These first carbonates formed the outer walls of the pipes and continued to grow inward, leading to self‐sustaining and self‐reinforcing focused fluid flow. The results, supported by literature‐based carbon and oxygen isotope analyses of the carbonates, indicate that ambient seawater and advected fresh/brackish water were involved in the carbonate precipitation by microbial methane oxidation. Similar structures may also form in modern settings where focused fluid flow advects fluids into overlying sand‐dominated formations, which has wide implications for the understanding of how focusing of fluids works in sedimentary basins with broad consequences for the migration of water, oil and gas.